2019
DOI: 10.1289/ehp5159
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Bisphenol A and Bisphenol S and Incident Type 2 Diabetes: A Case–Cohort Study in the French Cohort D.E.S.I.R.

Abstract: Background:The question of whether exposure to bisphenol A (BPA) contributes to the development of type 2 diabetes is still unresolved. Most epidemiological evidence on the association between BPA and diabetes is from cross-sectional studies or longitudinal studies with single urinary measurements. No prospective study has examined exposure to BPA analogs such as bisphenol S (BPS) in relation to incident type 2 diabetes.Objectives:We aimed to investigate whether exposure to BPA and BPS, assessed at up to two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 33 publications
4
49
0
Order By: Relevance
“…Another study aimed to determine the risk of developing T2D over a 9-year period in the French cohort called "Data from an Epidemiological Study on the Insulin Resistance Syndrome" (D.E.S.I.R). Of 755 participants, 201 cases of diabetes were diagnosed, and results suggested that participants in higher quartiles of BPA exposure had nearly double the risk of developing T2D (Rancière et al, 2019). Overall, available data provide strong evidence supporting a link between bisphenol exposure and MetS.…”
Section: Exposure To Plasticizers and Risk For Metabolic Syndrome: Epmentioning
confidence: 89%
“…Another study aimed to determine the risk of developing T2D over a 9-year period in the French cohort called "Data from an Epidemiological Study on the Insulin Resistance Syndrome" (D.E.S.I.R). Of 755 participants, 201 cases of diabetes were diagnosed, and results suggested that participants in higher quartiles of BPA exposure had nearly double the risk of developing T2D (Rancière et al, 2019). Overall, available data provide strong evidence supporting a link between bisphenol exposure and MetS.…”
Section: Exposure To Plasticizers and Risk For Metabolic Syndrome: Epmentioning
confidence: 89%
“…Now a longitudinal study published in Environmental Health Perspectives , examining not just BPA but also its widely used substitute bisphenol S (BPS), adds to the evidence. 7 The study found positive associations between incidence of diabetes and exposure to both BPA and BPS, independent of traditional risk factors.…”
mentioning
confidence: 80%
“…BPA has been considered a risk factor in the etiology of type 2 diabetes (T2D) (Alonso-Magdalena et al, 2006;Ropero et al, 2008;Nadal et al, 2009;Batista et al, 2012). Epidemiological and prospective studies associated BPA exposure with alterations in glucose homeostasis or T2D incidence, independently of obesity or other traditional factors (Lang et al, 2008;Shankar and Teppala, 2011;Beydoun et al, 2014;Ranciere et al, 2019). Recent epidemiological data associated BPS urine levels with T2D development in a case-cohort study (Ranciere et al, 2019) and a case-control study (Duan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and prospective studies associated BPA exposure with alterations in glucose homeostasis or T2D incidence, independently of obesity or other traditional factors (Lang et al, 2008;Shankar and Teppala, 2011;Beydoun et al, 2014;Ranciere et al, 2019). Recent epidemiological data associated BPS urine levels with T2D development in a case-cohort study (Ranciere et al, 2019) and a case-control study (Duan et al, 2018). BPF has been recently associated with abdominal 58 obesity in children (Jacobson et al, 2019), but association with T2D is still unclear.…”
Section: Introductionmentioning
confidence: 99%